The role of 5-HTergic neuron activation in the rapid antidepressant-like effects of hypidone hydrochloride (YL-0919) in mice - Li, Guang-Xiang; Yan, Jiao-Zhao; Sun, Sun-Rui; Hou, Xiao-Juan; Yin, Yong-Yu; Li, Yun-Feng (Frontiers in Pharmacology, 2024)
Major depressive disorder (MDD) is a common and disabling mental health condition; the currently available treatments for MDD are insufficient to meet clinical needs due to their limited efficacy and slow onset of action. Hypidone hydrochloride (YL-0919) is a sigma-1 receptor agonist and a novel fast-acting antidepressant that is currently under clinical development. To further understand the fast-acting antidepressant activity of YL-0919, this study focused on the role of 5-HTergic neurons in the dorsal raphe nucleus (DRN) in mice. Using fiber photometry to assess neural activity in vivo and two behavioral assays (tail suspension test and forced swimming test) to evaluate antidepressant-like activity, it was found that 3 or 7 days of YL-0919 treatment significantly activated serotonin (5-HT) neurons in the DRN and had significant antidepressant-like effects on mouse behaviors. Chemogenetic inhibition of 5-HTergic neurons in the DRN significantly blocked the antidepressant-like effect of YL-0919. In addition, YL-0919 treatment significantly increased the 5-HT levels in the prefrontal cortex (PFC). These changes were drastically different from those of the selective serotonin reuptake inhibitor (SSRI) fluoxetine, which suggested that the antidepressant-like effects of the two compounds were mechanistically different. Together, these results reveal a novel role of 5-HTergic neurons in the DRN in mediating the fast-acting antidepressant-like effects of YL-0919, revealing that these neurons are potential novel targets for the development of fast-acting antidepressants for the clinical management of MDD.